Interactive Case-Based Childhood Adversity and Trauma-Informed Care Electronic Modules for Pediatric Primary Care - Binny Chokshi; Kuan-Lung Daniel Chen; Lee Beers (Association of American Medical Colleges, 2020)
Introduction Training health professionals for the skills and capacity to respond adequately to children and adults who have been exposed to adverse childhood experiences is recognized as an essential need in health care. Accessible opportunities to educate physicians and physician-trainees are limited. Methods Four computer-based e-modules were created focusing on addressing childhood adversity and implementing trauma-informed care in the pediatric primary care setting. These childhood adversity and trauma-informed care (CA-TIC) e-modules were designed as an individualized, self-directed experience to allow for distance learning with flexibility to be embedded into existing coursework. To foster an engaging learning environment, we narrated the modules, prioritized images, and included the opportunity for participant interaction via multiple-choice and short-answer questions. Twenty-eight pediatric residents, two medical students, four attending physicians, and one fellow at Children's National Hospital completed the e-modules. Results Overall, participants rated the CA-TIC e-modules 4.6 (SD = 0.5) out of 5 for design and quality. Using paired t tests and Wilcoxon signed rank tests, we found statistically significant score increases from presession to postsession for participants' knowledge, attitudes, practice, and confidence related to CA-TIC. The most commonly cited learning points and practice changes included asking about trauma in practice and the seven C's of resilience. Discussion A trauma-informed, strengths-based approach to care can assist health care providers in mitigating the link between adversity and related poor health outcomes. The CA-TIC e-modules provide an opportunity to train health professionals using an innovative, self-directed, and low-resource mechanism.